Postoperative paralytic ileus following debulking surgery in ovarian cancer patients - Egger, Eva K.; Merker, Freya; Ralser, Damian J.; Marinova, Milka; Vilz, Tim O.; Matthaei, Hanno; Hilbert, Tobias; Mustea, Alexander (Frontiers in Surgery, 2022)
Aim: Evaluation of the incidence of postoperative ileus (POI) following cytoreductive surgery in epithelial ovarian cancer (EOC) patients and its impact on anastomotic leakage occurrence and postoperative complications. Methods: 357 surgeries were performed in 346 ovarian cancer patients in between 1/2010 to 12/2020 at our institution. The postoperative course regarding paralytic ileus, anastomotic leckage and postoperative complications was analyzed by Fisher`s exact test and through ordinal logistic regression. Results: 233 patients (65.3%) returned to normal gastrointestinal functions within 3 days after surgery. 123 patients (34.5%) developed a POI. There were 199 anastomoses in 165 patients and 24 leckages (12.1%). Postoperative antibiotics (p 0.001), stoma creation (p 0.0001) and early start of laxatives (p 0.0048) significantly decreased POI, while anastomoses in general (p 0.0465) and especially low anastomoses (p 0.0143) showed increased POI rates. Intraoperative positive fluid excess > 5000cc was associated with a higher risk for a POI (p 0.0063), anastomotic leckage (p 0.0254) and severe complications (p 0.0012). Conclusion: Postoperative antibiotics, an early start with laxatives and a stoma creation were associated with reduced POI rates. Patients with anastomoses showed an increased risk for a POI. Severe complications, anastomotic leckages and POI were more common in case of an intraoperative fluid balance exceeding 5000 cc.